Paper Review for Application of Thermally Treated Eggshell Waste: Systematic Approach - Estrada, Yiesha Kyra N. (Animo Repository, 2021)
The amount of eggshell waste continues to rise due to the increased consumption of eggs; thus, finding methods to repurpose these waste materials would be beneficial. The estimated number of eggshell wastes in the Philippines for 2019 is 63.28 thousand metric tons. Moreover, eggshells also exhibit potential to have various applications due to their polycrystalline structure and calcite crystal content. The performance of eggshells in these applications can be maximized through thermal treatment, which involves exposing the eggshells to high temperatures for a period of time. Thus, this study aims to develop a framework using systematic mapping approach to evaluate the application of calcined eggshells. Through this method, relevant papers were collated, screened, analyzed, and evaluated. The findings showed that the application of calcined eggshells can be classified into seven general utilizations: catalysis, adsorption, additives, hydroxyapatite synthesis, bacteria removal, biogas production, and biomass gasification. Additionally, the resulting data indicated that chicken eggshells were the most used eggshell type for these applications. It was also noted that the usual temperature and time for thermal treatment ranges from around 500-1000°C for about 2-4 hours. Overall, the results suggest the possibility for eggshells, given the significant eggshell waste production in the country, to be utilized in different applications through thermal treatment.